Pengaruh Campuran Pupuk Organik Cair Limbah Buah dengan Nutrisi AB Mix terhadap Pertumbuhan Bayam Merah (Alternantera Amoena Voss) pada Sistem Hidroponik Static Aerated Technique - Simamora, Kristian Gerenaldo; Tusi, Ahmad; Amien, Elhamida Rezkia; Triyono, Sugeng (Jurnal Agricultural Biosystem Engineering, 2025)
The high volume of fruit waste in Lampung and Indonesia in general requires environmentally friendly waste management solutions. This study aims to utilize such waste for liquid organic fertilizer by evaluating the effects of mixing fruit waste-based liquid organic fertilizer (LOF) with AB Mix nutrients on the growth of red spinach (Alternanthera amoena Voss) in a Static Aerated Technique (SAT) hydroponic system. The research employed a Completely Randomized Design (CRD) with a single factor, consisting of five treatment combinations of LOF and AB Mix concentrations (0–100%) and three replications. Observed parameters included plant height, number of leaves, plant weight, root length and weight, stem diameter, and water use efficiency. The results showed that the use of pure AB Mix (100%) produced the best growth outcomes compared to the mixed or pure LOF treatments. The lower growth and productivity in the LOF treatments were attributed to the low levels of macronutrients (N, P, K) in the produced LOF, as well as the presence of sediment that hindered nutrient absorption and the upward flow of nutrient solution from the reservoir to the plant root zone. Nevertheless, the combination of LOF and AB Mix still shows potential as an alternative nutrient source for hydroponic cultivation if optimally formulated.  Keywords:  AB Mix, Fruit Waste, Liquid Organic Fertilizer, Red Spinach, SAT Hydroponics,